2020
DOI: 10.2174/1874303x02013010001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Non-Alcoholic Fatty Liver and Chronic Kidney Disease

Abstract: Background: NAFLD is an independent risk factor of CKD. CKD prevalences in NAFLD subjects are two times higher than non-NAFLD. The aim of this study is to know the correlation between NAFLD and CKD. Methods: Cross-sectional study was conducted on patients who held Abdominal USG in Wahidin Sudirohusodo & UNHAS hospital from January to December 2017. NAFLD subjects are male and female (18-60 years) who met NAFLD cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Kasim et al . 35 also found more grade 3 CKD patients in the NAFLD group than in the control group (37.3% vs. 9.0%).…”
Section: Effects Of Nafld On Ckd Severitymentioning
confidence: 71%
See 1 more Smart Citation
“…Kasim et al . 35 also found more grade 3 CKD patients in the NAFLD group than in the control group (37.3% vs. 9.0%).…”
Section: Effects Of Nafld On Ckd Severitymentioning
confidence: 71%
“…34 Ramadhan et al 58 found that the presence of liver fibrosis increased the CKD risk by approximately 3.8 times in patients with NAFLD (95% CI: 1.07-13.79, p=0.035); meanwhile, the frequency of grades 2 and 3 CKD was higher in patients with liver fibrosis than in those without (p=0.034). Kasim et al 35 also found more grade 3 CKD patients in the NAFLD group than in the control group (37.3% vs. 9.0%).…”
Section: Effects Of Nafld On Ckd Severitymentioning
confidence: 88%
“…14 Studies have shown NAFLD as an independent risk factor and contributes to the development of CKD. 15 BMI was also evaluated. It shows that the majority of patients having a mild reduction in GFR or a stage II kidney disease, also had an increased BMI.…”
Section: Discussionmentioning
confidence: 99%